Analisis Strategi Pemasaran Sayuran Hidroponik (Studi Kasus CV DewaPonik Yogyakarta) - endah cahyaning astuti (Universitas Muhammadiyah Purwokerto, 2022)
Hydroponic vegetable cultivation is a growing business. Higher selling prices compared to vegetables in general and consumer interest in hydroponic vegetables are opportunities for profit. The purpose of this study was to determine marketing strategies and efforts to increase the competitiveness of hydroponic vegetables. This research is a case study at CV DewaPonik which operates hydroponic vegetables in Bantul Regency. The data analysis method used SWOT matrix analysis. The results showed that the highest value weighting result of 3.92 was in quadrant 1, by developing the Strength – Opportunity (S – O) strategy as the main priority. CV DewaPonik needs to improve the quality of hydroponic vegetable products so that they can compete with other farmers and need to add types of vegetables so that consumers can buy various types of vegetables. Target consumers need to be expanded by marketing hydroponic vegetable products to restaurants, hotels and supermarkets.